Quinolinic Acid and Nuclear Factor Erythroid 2-Related Factor 2 in Depression: Role in Neuroprogression - Bansal, Yashika; Singh, Raghunath; Parhar, Ishwar; Kuhad, Anurag; Soga, Tomoko (Frontiers in Pharmacology, 2019)
Depression is an incapacitating neuropsychiatric disorder. The serotonergic system in the brain plays an important role in the pathophysiology of depression. However, due to the often delayed and/or poor performance of selective serotonin reuptake inhibitors in treating depressive symptoms, the serotonergic system’s role in depression has recently been questioned further. Evidence from recent studies has suggested that increased inflammation and oxidative stress may play significant roles in the pathophysiology of depression. The consequences of these factors can lead to the neuroprogression of depression, which includes neurodegeneration, astrocyte apoptosis, reduced neurogenesis, reduced plasticity (neuronal and synaptic), and enhanced immunoreactivity. Specifically, increased proinflammatory cytokine levels have been shown to lead to the activation of the kynurenine pathway, which causes an increase in the production of quinolinic acid [QA, an N-Methyl-D-aspartate (NMDA) agonist] and decreases the synthesis of serotonin. QA exerts many deleterious effects in the brain via mechanisms including NMDA excitotoxity, increased oxidative stress, astrocyte degeneration, and neuronal apoptosis. QA may also act directly as a pro-oxidant. Additionally, the nuclear translocation of antioxidant defence factors, such as nuclear factor (erythroid-derived 2)-like 2 (Nrf2), is downregulated in depression. Hence, in the present review, we discuss the role of QA in increasing oxidative stress in depression by modulating the nuclear translocation of Nrf2 and thus affecting the synthesis of antioxidant enzymes.